Persepsi Petani Terhadap Pengelolaan Hutan Rakyat Campaka di Kabupaten Minahasa - Matitaputty, Desly Rolando; Langi, Martina A.; Walangitan, Hengki D. (Sam Ratulangi University, 2023)
This research aims to determine the farmers' perceptions of managing the Cempaka community forest in Minahasa District. The study was conducted for five months, from December 2022 to April 2023. The selection of respondents was intentional. The data used in this research includes primary and secondary data. Primary data was collected through interviews using questionnaires administered to 98 community forest farmers in Minahasa District. The collected data includes the characteristics of the community forest, such as the respondents' characteristics (ethnicity, gender, age, education level, number of dependents, monthly income, principal occupation, membership in forest farmer groups, and the intensity of extension services), as well as the characteristics of the community forest, such as the applied community forest patterns, land area, land status, and the farmers' perceptions of the management of the Cempaka community forest. The farmers' perceptions were assessed based on their knowledge of Cempaka, and the functions of the community forest were evaluated from four aspects: social-cultural, conservation and ecological, economic, and regulatory. Secondary data were obtained from reports and journal articles that support the research topic. The research findings indicate that the level of perception among community forest farmers in Minahasa District is categorized as high. This means that the farmers have a good understanding of Cempaka and the functions of the Cempaka community forest in terms of social-cultural, ecological and conservation, economic, and regulatory aspects. The cultivation of Cempaka is a genetic legacy that needs to be preserved and passed down to future generations. Therefore, the functions of the community forest should not only be seen from an economic perspective but also in terms of preserving local tree species. Government support in developing the Cempaka community forest is crucial, particularly in terms of policy regulation.